Fourier transform infrared spectroscopy of low-k dielectric material on patterned wafers - Huang, Maggie Y. M. (2013)
With many of research on Fourier transform IR (FTIR) on low-k materials, our experiments extended the FTIR spectroscopy application to characterization and analysis of the low-k dielectric thin film properties on patterned wafers. FTIR spectra on low-k materials were successfully captured under three sampling modes: reflection, attenuated total reflectance (ATR), and mapping mode. ATR mode is more suitable for CHx band than reflection mode due to its higher sensitivity in this range. FTIR spectroscopy signal analysis on mixed structures (metal and low-k dielectric material) on patterned wafers was also investigated with mapping mode. Based on our investigation, FTIR can be used for low-k material studies on patterned wafer.